PENGARUH KEPEMIMPINAN YANG MELAYANI DAN IKLIM KERJA TERHADAP KINERJA MELALUI MOTIVASI (STUDY PADA DINAS PERHUBUNGAN KABUPATEN KENDAL) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze Servant leadership and influence the working climate of the performance through motivation District Department of Transportation in Kendal. This research uses field research (field research ) , with a quantitative approach . The population in this reserach was the employees of Dinas Perhubungan, it’s about 76 employees. The sample used in this study is the total population of of Dinas Perhubungan totaling 74 respondents  ( the leader and researcher are not as respondents ) . this analysis technique used linear analysis model testing , Test R2 , F-test , testing the hypothesis used the t test. The results showed that, (1) the servant leadership positive effect on the motivation of employees  (2) Work climate positive effect on motivation,(3) the servant leadership does’t  positive effect on employee performance, (4) Work climate positive effect on the performance of employee 5) Motivation has positive effect on the performance of employee.Keywords: Servant Leadership, Work Climate, Motivation, and Performance of Employee